Claiming Knowledge, Strategies of Epistemology from Theosophy to the New Age. - Olav Hammer (Numen Book Series Online, ISBN: 9789004380837., 2004)
This volume deals with the transformation of religious creativity in the late modern West. Its point of departure is a set of esoteric beliefs, from Theosophy to the New Age. It shows how these traditions have adapted to the cultural givens of each successive epoch. The claims of each movement have been buttressed by drawing on various structural characteristics of late modernity. The advance of science has resulted in attempts to claim scientific status for religious beliefs. Globalization has given rise to massive loans from other cultures, but also to various strategies to radically reinterpret foreign elements. Individualism has led to an increasing reliance on experience as a source of legitimacy. The analytical tools applied to understanding religious modernization shed light on changes that are fundamentally reshaping many religious traditions. This publication has also been published in hardback, please click here for details.